O que o artista faz com o que a televisão faz com a arte? - Freire, Bruno Farias de Mello (2012)
In the era of mobile communication, television is adapting. Viewers watch TV in transit on portable devices. New technologies diversify communication, providing more free and democratic practices. However, the most influential opinion makers still focus on the same platforms of yore. Some datas shows that 75% of Brazilians have on open TV their main source of information about politics (BAVA, 2010). Increasingly, TV acts body-to-body, inserting itself in daily life, promoting a dance of habits. The hypothesis of this project is that we are being choreographed by our daily contact with television, which also teaches us what an artist is and how art should be. We use the concept of social choreography (HEWITT, 2005) to argue that the values prevailing in society and choreography alter our bodily habits, inside and out television. This hypothesis is based on two themes: the understanding that there is a co-dependency between body and environment, explained by the Corpomídia s Theory (KATZ and GREINER, 2004), and that the mediations involved there go towards BARBERO s proposal (1997). In contemporary society, the profession of an artist has lost the ability to have a concrete social status (AGAMBEN, 1974/2012), making it an abstract adjective that can be applied to anyone. The object of the research is the program schedule of TV Globo, SBT and Record, and his goal, to investigate the social choreography they promote regarding the understanding of what an artist is. The second chapter makes a poetic exercise that proposes a form of relationship between art and communication. The third chapter is a pilot project for TV, a possibility of intervention and development of academic s issues inside society